5.2.17 Problems 1601 to 1700

Table 5.201: Second order linear ODE

#

ODE

Mathematica

Maple

7968

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-2 y = 0 \]

7969

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-16 y = 0 \]

7970

\[ {}y^{\prime \prime }+3 y^{\prime }-10 y = 6 \,{\mathrm e}^{4 x} \]

7971

\[ {}y^{\prime \prime }+4 y = 3 \sin \left (x \right ) \]

7972

\[ {}y^{\prime \prime }+10 y^{\prime }+25 y = 14 \,{\mathrm e}^{-5 x} \]

7973

\[ {}y^{\prime \prime }-2 y^{\prime }+5 y = 25 x^{2}+12 \]

7974

\[ {}y^{\prime \prime }-y^{\prime }-6 y = 20 \,{\mathrm e}^{-2 x} \]

7975

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = 14 \sin \left (2 x \right )-18 \cos \left (2 x \right ) \]

7976

\[ {}y^{\prime \prime }+y = 2 \cos \left (x \right ) \]

7977

\[ {}y^{\prime \prime }-2 y^{\prime } = 12 x -10 \]

7978

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 6 \,{\mathrm e}^{x} \]

7979

\[ {}y^{\prime \prime }-2 y^{\prime }+2 y = {\mathrm e}^{x} \sin \left (x \right ) \]

7980

\[ {}y^{\prime \prime }+y^{\prime } = 10 x^{4}+2 \]

7981

\[ {}y^{\prime \prime }+4 y = 4 \cos \left (2 x \right )+6 \cos \left (x \right )+8 x^{2}-4 x \]

7982

\[ {}y^{\prime \prime }+9 y = 2 \sin \left (3 x \right )+4 \sin \left (x \right )-26 \,{\mathrm e}^{-2 x}+27 x^{3} \]

7983

\[ {}y^{\prime \prime }-3 y = {\mathrm e}^{2 x} \]

7985

\[ {}y^{\prime \prime }+4 y = \tan \left (2 x \right ) \]

7986

\[ {}y^{\prime \prime }+2 y^{\prime }+y = {\mathrm e}^{-x} \ln \left (x \right ) \]

7987

\[ {}y^{\prime \prime }-2 y^{\prime }-3 y = 64 x \,{\mathrm e}^{-x} \]

7988

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = {\mathrm e}^{-x} \sec \left (2 x \right ) \]

7989

\[ {}2 y^{\prime \prime }+3 y^{\prime }+y = {\mathrm e}^{-3 x} \]

7990

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = \frac {1}{1+{\mathrm e}^{-x}} \]

7991

\[ {}y^{\prime \prime }+y = \sec \left (x \right ) \]

7992

\[ {}y^{\prime \prime }+y = \cot \left (x \right )^{2} \]

7993

\[ {}y^{\prime \prime }+y = \cot \left (2 x \right ) \]

7994

\[ {}y^{\prime \prime }+y = x \cos \left (x \right ) \]

7995

\[ {}y^{\prime \prime }+y = \tan \left (x \right ) \]

7996

\[ {}y^{\prime \prime }+y = \sec \left (x \right ) \tan \left (x \right ) \]

7997

\[ {}y^{\prime \prime }+y = \sec \left (x \right ) \csc \left (x \right ) \]

7998

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 2 x \]

7999

\[ {}y^{\prime \prime }-y^{\prime }-6 y = {\mathrm e}^{-x} \]

8000

\[ {}\left (x^{2}-1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = \left (x^{2}-1\right )^{2} \]

8001

\[ {}\left (x^{2}+x \right ) y^{\prime \prime }+\left (-x^{2}+2\right ) y^{\prime }-\left (x +2\right ) y = x \left (1+x \right )^{2} \]

8002

\[ {}\left (1-x \right ) y^{\prime \prime }+x y^{\prime }-y = \left (1-x \right )^{2} \]

8003

\[ {}x y^{\prime \prime }-\left (1+x \right ) y^{\prime }+y = x^{2} {\mathrm e}^{2 x} \]

8004

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }+2 y = x \,{\mathrm e}^{-x} \]

8005

\[ {}y^{\prime \prime }+y = 0 \]

8006

\[ {}y^{\prime \prime }-y = 0 \]

8007

\[ {}x y^{\prime \prime }+3 y^{\prime } = 0 \]

8008

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-4 y = 0 \]

8009

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

8010

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

8011

\[ {}y^{\prime \prime }-\frac {x y^{\prime }}{x -1}+\frac {y}{x -1} = 0 \]

8012

\[ {}x^{2} y^{\prime \prime }+2 x y^{\prime }-2 y = 0 \]

8013

\[ {}x^{2} y^{\prime \prime }-x \left (x +2\right ) y^{\prime }+\left (x +2\right ) y = 0 \]

8014

\[ {}y^{\prime \prime }-x f \left (x \right ) y^{\prime }+f \left (x \right ) y = 0 \]

8015

\[ {}x y^{\prime \prime }-\left (2 x +1\right ) y^{\prime }+\left (1+x \right ) y = 0 \]

8039

\[ {}y^{\prime \prime }-3 y^{\prime }+y = 0 \]

8040

\[ {}y^{\prime \prime }+y^{\prime }+y = 0 \]

8041

\[ {}y^{\prime \prime }+6 y^{\prime }+9 y = 0 \]

8042

\[ {}y^{\prime \prime }-y^{\prime }+6 y = 0 \]

8043

\[ {}y^{\prime \prime }-2 y^{\prime }-5 y = x \]

8044

\[ {}y^{\prime \prime }+y = {\mathrm e}^{x} \]

8045

\[ {}y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right ) \]

8046

\[ {}y^{\prime \prime }-y = {\mathrm e}^{3 x} \]

8047

\[ {}y^{\prime \prime }+9 y = 0 \]

8048

\[ {}y^{\prime \prime }-y^{\prime }+4 y = x \]

8049

\[ {}y^{\prime \prime }+2 y^{\prime }+5 y = {\mathrm e}^{x} \]

8050

\[ {}y^{\prime \prime }+3 y^{\prime }+4 y = \sin \left (x \right ) \]

8051

\[ {}y^{\prime \prime }+y = {\mathrm e}^{-x} \]

8052

\[ {}y^{\prime \prime }-y = \cos \left (x \right ) \]

8053

\[ {}y^{\prime \prime } = \tan \left (x \right ) \]

8054

\[ {}y^{\prime \prime }-2 y^{\prime } = \ln \left (x \right ) \]

8055

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = 2 x -1 \]

8056

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = {\mathrm e}^{-x} \]

8057

\[ {}y^{\prime \prime }-y^{\prime }-2 y = \cos \left (x \right ) \]

8058

\[ {}y^{\prime \prime }+2 y^{\prime }-y = x \,{\mathrm e}^{x} \sin \left (x \right ) \]

8059

\[ {}y^{\prime \prime }+9 y = \sec \left (2 x \right ) \]

8060

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = x \ln \left (x \right ) \]

8061

\[ {}x^{2} y^{\prime \prime }+3 x y^{\prime }+y = \frac {2}{x} \]

8062

\[ {}y^{\prime \prime }+4 y = \tan \left (x \right )^{2} \]

8063

\[ {}y^{\prime \prime }-y = 3 \,{\mathrm e}^{2 x} \]

8064

\[ {}y^{\prime \prime }+y = -8 \sin \left (3 x \right ) \]

8065

\[ {}y^{\prime \prime }+y^{\prime }+y = x^{2}+2 x +2 \]

8066

\[ {}y^{\prime \prime }+y^{\prime } = \frac {x -1}{x} \]

8067

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

8068

\[ {}y^{\prime \prime }+9 y = -3 \cos \left (2 x \right ) \]

8070

\[ {}y^{\prime \prime } = -3 y \]

8167

\[ {}y^{\prime \prime }+5 y^{\prime }+6 y = 5 \,{\mathrm e}^{3 t} \]

8168

\[ {}y^{\prime \prime }+y^{\prime }-6 y = t \]

8169

\[ {}y^{\prime \prime }-y = t^{2} \]

8173

\[ {}y^{\prime \prime }+3 y^{\prime }-5 y = 1 \]

8174

\[ {}y^{\prime \prime }+3 y^{\prime }-2 y = -6 \,{\mathrm e}^{-t +\pi } \]

8175

\[ {}y^{\prime \prime }+2 y^{\prime }-y = t \,{\mathrm e}^{-t} \]

8176

\[ {}y^{\prime \prime }-y^{\prime }+y = 3 \,{\mathrm e}^{-t} \]

8177

\[ {}y^{\prime \prime }-5 y^{\prime }+4 y = 0 \]

8178

\[ {}y^{\prime \prime }+3 y^{\prime }+3 y = 2 \]

8179

\[ {}y^{\prime \prime }+y^{\prime }+2 y = t \]

8180

\[ {}y^{\prime \prime }-7 y^{\prime }+12 y = t \,{\mathrm e}^{2 t} \]

8181

\[ {}i^{\prime \prime }+2 i^{\prime }+3 i = \left \{\begin {array}{cc} 30 & 0<t <2 \pi \\ 0 & 2 \pi \le t \le 5 \pi \\ 10 & 5 \pi <t <\infty \end {array}\right . \]

8219

\[ {}y^{\prime \prime }+y = 0 \]

8221

\[ {}y^{\prime \prime }-y = 0 \]

8223

\[ {}y^{\prime \prime }-y^{\prime } = 0 \]

8225

\[ {}y^{\prime \prime }+2 y^{\prime } = 0 \]

8287

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{9}\right ) y = 0 \]

8288

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-1\right ) y = 0 \]

8289

\[ {}4 x^{2} y^{\prime \prime }+4 x y^{\prime }+\left (4 x^{2}-25\right ) y = 0 \]

8290

\[ {}16 x^{2} y^{\prime \prime }+16 x y^{\prime }+\left (16 x^{2}-1\right ) y = 0 \]

8291

\[ {}x y^{\prime \prime }+y^{\prime }+x y = 0 \]

8292

\[ {}y^{\prime }+x y^{\prime \prime }+\left (x -\frac {4}{x}\right ) y = 0 \]